Market Conditions as One of the Factors Influencing the Formation of an Enterprise's Cash Flows - Qudratovich, Eshonqulov Akmal (Research Parks Publishing LLC, 2023)
This article explores the impact of market conditions on the cash flow of businesses. It highlights the importance of cash flow management in the success of a business and explains how competition, changes in the economy, and industry trends can influence pricing and cash flow. The article also offers practical suggestions for businesses to improve their cash flow management in response to market conditions. By developing contingency plans, monitoring cash flow regularly, forecasting future cash flow, diversifying product or service offerings, improving marketing and sales strategies, and implementing cost-saving measures, businesses can position themselves for success in uncertain market conditions. The article concludes by reiterating the importance of market conditions in cash flow management and highlighting the need for businesses to remain vigilant in their approach to cash flow management.